Perwujudan Profesionalitas Jabatan Notaris Berdasarkan Undang-Undang Nomor 2 Tahun 2014 atas Perubahan Undang-Undang Nomor 30 Tahun 2004 di Kabupaten Ngawi - MS, Nuruzzaman; Fatimah, Siti (Zaaken: Journal of Civil and Business Law, 2024)
The importance of Notary's duties relating to law requires the ability and professionalism. the implementation of professionalism of Notary's office based on Law no. 2 Year 2014. Notaries that not only uphold and promote justice and truth according to law, but also must rely on good ethics and morality as public officials. The inaccuracy and lack of professionalism of Notaries precisely coalesce and enforce law enforcement, legal certainty and rule of law in the State of the Republic of Indonesia. The results of this study indicate in carrying out its duties both in terms of authority or obligations, the notary must be responsible for the duties, that is, the notary is required to make the deed with good and true, means that the deed made has fulfilled the legal will and the request of the parties concerned because of his position; Notary is required to produce a quality deed, meaning that the deed is made according to the rule of law and the will of the interested parties in a real sense, not to make it up. The Notary must explain to the parties to the truth about the contents and procedures of the deed which he made; and have a positive impact, meaning that anyone will recognize the notarial deed has perfect proof of power.